PENGARUH PENDAPATAN ASLI DAERAH DARI SEKTOR PARIWISATA DALAM MENINGKATKAN PEREKONOMIAN KABUPATEN KOLAKA - Andi Elma Liana; Amir Sahaka; Suhardin Suhardin (IAI Al-Mawaddah Warrahmah Kolaka, 2020)
Tourism is a sector with great potential in contributing to improving the economy of a country. According to Law No. 10 of 2009 concerning tourism, tourism is an activity that aims at organizing tourism services, providing tourist objects and attractions. The formulation of the problem in this research is whether there is an effect of local revenue from the tourism sector in improving the economy of Kolaka Regency and also how are the supporting and inhibiting factors for development of the tourism sector in Kolaka Regency. The purpose of this study is to determine whether there is an effect of local revenue from the tourism sector in improving the economy of Kolaka Regency and also to determine the obstacles or obstacles experienced by the tourism sector as well as supporting factors for tourism development in Kolaka Regency.The research method used is a type of quantitative research with a quantitative approach with the subject of local revenue from the tourism sector in improving the economy of Kolaka Regency. Then the research procedure carried out includes intensive observation (questionnaires, interviews, and documentation) about the local revenue from the tourism sector in improving the economy of Kolaka Regency.The results of this study indicate that local revenue from the tourism sector has an influence in improving the economy of Kolaka Regency, this is evidenced by the results obtained from the SPSS application which functions to test the questionnaire that has been filled in by employees in the form of statements.